From COVID-19 Pandemic to Entrepreneurial Behavior: The Mediating Effect of Proactive Personality and the Moderating Role of Anticipated Regret - Wang Jiatong; Majid Murad; Fu Bajun; Nausheen Syed; Muhammad Munir (Frontiers in Psychology, 2022)
COVID-19 is a global public health issue that poses a challenge to the education sector. The pandemic has a devastating impact on student entrepreneurial behavior and their mental health. This study aimed to examine the impact of COVID-19 on the student entrepreneurial intention/behavioral model with a mediating effect of proactive personality and the moderating role of anticipated regret. The sample of the study comprised 345 university students from Pakistan. Data were collected using a self-report and other report survey questionnaires. The hypotheses were investigated using the partial least squares structural equation modeling (PLS–SEM) approach. According to the findings, COVID-19 perception has a negative and significant impact on the student entrepreneurial intention/behavior model. Meanwhile, findings show that a proactive personality significantly mediates the relationship between COVID-19 perception and entrepreneurial intention. The results show that anticipated regret moderates the relationship between entrepreneurial intention and entrepreneurial behavior in a favorable and significant way. Furthermore, discussion and implications were also discussed in this article.